Performa motor bakar satu silinder dengan variasi oktan bahan bakar dan tekanan kompresi - Bahtiar Rahmat; Mohammad Burhan Rubai Wijaya; Yuris Bahadur Wirawan; Fahmy Zuhda Bahtiar (Jurnal Teknik Mesin Indonesia, 2023)
The performance of an internal combustion engine was greatly influenced by several factors, including the quality of the fuel and the compression pressure of the engine. High compression pressure, followed by the selection of the appropriate fuel octane number, would result in optimal performance. Conversely, an engine with a high compression pressure given fuel with a low octane number would produce poor performance. Unfortunately, only few users know that high compression engines require fuel with high octane numbers. The purpose of this study was to determine the difference in the power & torque output of single-cylinder combustion engine given variations in compression pressure using pertamax (RON 92) & pertamax plus (RON 95) fuel. A dynamometer test has performed to determine the difference in engine performance. The results showed that the engine with high compression pressure (11.8 kg/cm2) with RON 95 fuel produced the highest power output of 7.5 kW with the highest torque output of 9.6 Nm. While the engine with low compression pressure (10 kg/cm2) using RON 92 fuel produced the lowest power output of 4.2 kW with the lowest torque output of 3.8 Nm.